Pengolahan Limbah Botol Plastik Menjadi Barang Yang Bernilai Ekonomis Untuk Meningkatkan Minat Menabung Siswa SD Negeri 56 Kelurahan Tihu, Kota Ambon - Ronald Darlly Hukubun; Stefano M. A. Rijoly; Aldeva H. F Mawuntu; Esra Yudha Empra; Safitriyani Safitriyani; Yayan Asmawan; Laury Marcia Ch. Huwae (Lembaga Pengembangan Kinerja Dosen, 2024)
Reusing used mineral water bottles as material for making piggy banks is a popular way to teach children about the importance of saving from an early age. This practice also has the added benefit of reducing the amount of plastic waste scattered around the living environment. Plastic waste that is not managed properly can cause serious environmental pollution. The service activity at Primary School 56, Tihu Subdistrict regarding making piggy banks from used bottles aims to train children's skills in processing used goods into something useful, but also to teach the importance of saving from an early age. Making piggy banks from used bottles is an opportunity for children to develop their creativity by utilizing used items into useful products. Through this activity, children can learn while being creative, understanding the importance of protecting the environment and managing waste better, as well as motivating them to like saving.